Digital Literacy in Navigating Historical Narratives in the Era of Disruption: Implications for Twenty First Century Local History Learning - Tati Haryati; Amrin Amrin (Council: Education Journal of Social Studies, 2026)
This study aims to analyze the role of digital literacy in Local History learning in the era of disruption by focusing on four key aspects: (1) students' utilization of digital historical sources, (2) their ability to evaluate the credibility of local historical narratives, (3) the development of historical thinking skills, and (4) the implications of digital literacy for twenty-first-century history education. This study employed a qualitative approach using a case study design conducted in the Local History course of the History Education Study Program. Data were collected through classroom observations, in-depth interviews, and document analysis, and were analyzed through data condensation, data display, and conclusion drawing and verification. The findings reveal that digital literacy encourages students to utilize a wide range of digital historical sources more critically and responsibly, enhances their ability to verify and evaluate the credibility of local historical narratives, and promotes the development of historical thinking through the use of historical evidence, contextual analysis, and evidence-based argumentation. Furthermore, the integration of digital literacy transforms Local History learning into a more participatory, collaborative, and inquiry-based learning process, thereby fostering essential twenty-first-century competencies, including critical thinking, communication, collaboration, creativity, and information literacy. This study concludes that digital literacy serves as a strategic competency in developing history learning that is adaptive to the era of disruption while strengthening the quality of twenty-first-century history education.